2007
DOI: 10.1111/j.1574-6968.2007.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Look on the positive side! The orientation, identification and bioenergetics of ‘Archaeal’ membrane-bound nitrate reductases

Abstract: Many species of Bacteria and Archaea respire nitrate using a molybdenum-dependent membrane-bound respiratory system called Nar. Classically, the 'Bacterial' Nar system is oriented such that nitrate reduction takes place on the inside of this membrane. However, the active site subunit of the 'Archaeal' Nar systems has a twin arginine ('RR') motif, which is a suggestion of translocation to the outside of the cytoplasmic membrane. These 'Archaeal' type of nitrate reductases are part of a group of molybdoenzymes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 43 publications
3
150
0
Order By: Relevance
“…Adjacent to the narC gene is a gene that encodes NarB, which is predicted to encode a Rieske iron-sulfur protein. The combination of NarB and NarC in H. mediterranei has led to the suggestion that nitrate respiration in some organisms might be driven by a Q-cycle mechanism (51). By coupling a Q-cycle mechanism to nitrate reduction would provide a pNAR system that is bioenergetically equivalent to the well characterized NAR (or nNAR) systems in bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjacent to the narC gene is a gene that encodes NarB, which is predicted to encode a Rieske iron-sulfur protein. The combination of NarB and NarC in H. mediterranei has led to the suggestion that nitrate respiration in some organisms might be driven by a Q-cycle mechanism (51). By coupling a Q-cycle mechanism to nitrate reduction would provide a pNAR system that is bioenergetically equivalent to the well characterized NAR (or nNAR) systems in bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the Q-cycle-coupling mechanism presented for selenate reduction in T. selenatis, while a novel mechanism for electron transport to molybdoenzymes in bacteria, might also be utilized in the Archaea (51). Sequence analysis has suggested that the clade of TAT-translocated type II molybdoenzymes, of which SER is a member, also contains a number of unusual respiratory nitrate reductases (pNAR).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the characteristics of these enzymes showed marked resemblance with the bacterial NarGH complex, underscoring the fact that there was a relevant difference related to the subcellular localization between the halophilic and bacterial enzymes (Yoshimatsu, Iwasaki, & Fujiwara 2002;Martinez-Espinosa et al, 2007).…”
Section: Respiratory Nitrate Reductases In Haloferax Genusmentioning
confidence: 98%
“…The Rieske/cytb complexes are energyconverting enzymes that operate between the initial electron donors and the terminal electron acceptors of respiratory chains. In halophiles, two distinct clusters of Rieske/cytb encoding genes have been described, (i) the Rieske/cytb complex cluster along with the NAR-encoding genes implied in the denitrifying chain (Martinez-Espinosa et al, 2007) and (ii) the Rieske/cytb complex cluster with a gene coding for an halocyanin followed by a cytochrome b (Nitschke et al, 2010). The implication of this second type of gene cluster in aerobic respiration seems the most likely function, where the halocyanin will work as an electron acceptor of the Rieske/ cytb complex and the donor to a cytochrome oxidase (Baymann et al, 2012).…”
Section: Inferred Metabolic and Ecological Featuresmentioning
confidence: 99%